The use of Islamic attribute in food product marketing: expert views - Osman, Suraiya; Ab. Rahman, Suhaimi; Abu Bakar, Elistina; Mohd Safian, Yasmin Hanani (Malaysian Consumer and Family Economics Association, 2024)
The vast number of Muslim consumers in Malaysia, which accounts for 63.5% of the total Malaysian population, offers a vast market segment to food producers—the food producers employ various marketing strategies to compete in the market. Among the strategies employed is the use of Islamic attributes in marketing activities. Food product marketers used Islamic attributes such as Muslim names, pictures, emblems, Quranic verses, and Hadith in their marketing campaigns. The free use of the Islamic attributes has drawn attention to knowing the Islamic perspective of the use. Through in-depth interviews, this research paper aimed to reveal the views of 7 Shariah experts in a rich and contextualized account of using Islamic attributes in food product marketing. The experts were selected through purposive and snowball sampling methods. Thematic analysis was used to analyze the data, which resulted in the emergence of six themes in this study. These themes include (1) protection of Islamic honor and dignity, (2) prohibition of using Islam for personal gain, (3) prohibition of unjust practices, (4) prohibition of superstitious or syirik acts, (5) promotion of good business practices, and (6) promotion of a healthy diet, revealing the Islamic perspective on its use. This study contributes knowledge to Islamic marketing and the rulings on using Islamic attributes according to the Shariah principle. This research sheds light on the ethical implications of using Islamic attributes in scholarly and marketing domains. Further, this research explores the triangulation method of data analysis and validity via Shariah and socio-research.